The Effect of Budget Participation and Information Asymmetry on Budgetary Slack with Dark Triad Character as a Moderating Variable in Hospitals in East Kalimantan - Setia Rahmi Yasmi; Yana Ulfah; Hariman Bone (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze the influence of budget participation and information asymmetry on budgetary slack, with Dark Triad characteristics as a moderating variable. The study was conducted in 54 hospitals in East Kalimantan, with 27 hospitals responding to the questionnaire. This research is included in the category of correlational research. The study sample consisted of 69 respondents, selected using the probability sampling method. Data was collected through the distribution of questionnaires via WhatsApp links, with a response period of two months. Data analysis was performed using the Structural Equation Modeling (SEM) - Partial Least Square (PLS) method, supported by Smart PLS software. The results show that budget participation has a positive and significant effect on budgetary slack. Additionally, information asymmetry also has a positive and significant effect on budgetary slack, meaning that the higher the information asymmetry, the greater the tendency for budgetary slack to occur. Furthermore, Dark Triad characteristics were found to moderate the relationship between budget participation and budgetary slack, as well as the relationship between information asymmetry and budgetary slack. In other words, individuals with Dark Triad traits tend to amplify the effects of budget participation and information asymmetry on the creation of budgetary slack. These findings emphasize the importance of strict supervision and effective budget control systems to minimize the negative impact of budgetary slack, particularly in organizational environments such as hospitals.